Otherness of place: Game-based interaction and learning in virtual heritage projects - Champion, Erik (Taylor Francis, 2008)
When we design digital places that represent the past using media such as game engines, it is all too easy to be taken in by the lure of technology and forget to concentrate on enhancing the user experience. In the case of virtual heritage, there are several important issues in the creation, construction or revocation of places of cultural significance. In this paper I will argue that while computer games do appear to be more successful learning environments than their critics give them credit for, the learning gained from using them is particularly dangerous in terms of the objectives of virtual heritage. I further suggest that computer games offer particular advantages over traditional virtual environment technology but that their typical modes of interaction must be re-examined, especially in relation to the notion of place.